Trichoderma asperellum empowers tomato plants and suppresses Fusarium oxysporum through priming responses - Sehim, Amira E.; Hewedy, Omar A.; Altammar, Khadijah A.; Alhumaidi, Maryam S.; Abd Elghaffar, Rasha Y. (Frontiers in Microbiology, 2023)
Plant-associated microbes play crucial roles in plant health and promote growth under stress. Tomato (Solanum lycopersicum) is one of the strategic crops grown throughout Egypt and is a widely grown vegetable worldwide. However, plant disease severely affects tomato production. The post-harvest disease (Fusarium wilt disease) affects food security globally, especially in the tomato fields. Thus, an alternative effective and economical biological treatment to the disease was recently established using Trichoderma asperellum. However, the role of rhizosphere microbiota in the resistance of tomato plants against soil-borne Fusarium wilt disease (FWD) remains unclear. In the current study, a dual culture assay of T. asperellum against various phytopathogens (e.g., Fusarium oxysporum, F. solani, Alternaria alternate, Rhizoctonia solani, and F. graminerarum) was performed in vitro. Interestingly, T. asperellum exhibited the highest mycelial inhibition rate (53.23%) against F. oxysporum. In addition, 30% free cell filtrate of T. asperellum inhibited F. oxysporum by 59.38%. Various underlying mechanisms were studied to explore the antifungal activity against F. oxysporum, such as chitinase activity, analysis of bioactive compounds by gas chromatography-mass spectrometry (GC-MS), and assessment of fungal secondary metabolites against F. oxysporum mycotoxins in tomato fruits. Additionally, the plant growth-promoting traits of T. asperellum were studied (e.g., IAA production, Phosphate solubilization), and the impact on tomato seeds germination. Scanning electron microscopy, plant root sections, and confocal microscopy were used to show the mobility of the fungal endophyte activity to promote tomato root growth compared with untreated tomato root. T. asperellum enhanced the growth of tomato seeds and controlled the wilt disease caused by the phytopathogen F. oxysporum by enhancing the number of leaves as well as shoot and root length (cm) and fresh and dry weights (g). Furthermore, Trichoderma extract protects tomato fruits from post-harvest infection by F. oxysporum. Taking together, T. asperellum represents a safe and effective controlling agent against Fusarium infection of tomato plants.